State crime and immorality : the corrupting influence of the powerful - Monaghan, Mark Peter; Prideaux, Simon (Policy Press, 2016)
This work examines the activities of UK and international 'role models' through the lens of state crime and social policy. Written by experts in the field of sociology and social policy, it provides a comprehensive discussion of state immorality and deviance generally and state crime in particular.